Patients' views of a multimedia resource featuring experiences of rheumatoid arthritis: pilot evaluation of www.healthtalkonline.org. - Newman, M; Ziebland, S; Barker, K (2009)
The Internet is used increasingly for health information and patient support. Online health information users gravitate to websites that feature patient experiences. However, experiential accounts may mislead if they are unrepresentative. The quality of experiential websites remains unexplored. Obtaining user feedback online can be problematic. This study explored views of www.dipex.org/arthritis, a website based on, and featuring, clips from interviews about experiences of rheumatoid arthritis (RA). Thirty-seven rheumatology outpatients viewed the site and completed a questionnaire. Overall the website appeared relevant and understandable and could be recommended. Comments highlighted the need to update the site regularly with experiences of new treatments; to ensure positive and negative experiences are balanced; and to ensure information is easy to find. The site has since been updated with new experiences and rewritten summaries that present a better balance of experiences. Changes were incorporated in an entire site redesign launched in autumn 2008 as www.healthtalkonline.org.